ANXIETY AND DEFENSE MECHANISM IN STEPHEN CHBOSKY’S NOVEL THE PERKS OF BEING A WALLFLOWER (PANOPTICON: Journal of English Studies, 2022)
This study entitled Anxiety and Defense Mechanism in Stephen Chboskyâ€™s Novel The Perks Of Being A Wallflower which discusses anxiety and defense mechanism that focuses on the novel written by Stephen Chbosky. The purpose of this study is to reveal the main character's anxiety through symptoms of anxiety based on Sigmund Freudâ€™s theory. In this study, the writer found several causes of anxiety such as; repression, environment, frustration, and fear were analyzed using Sigmund Freudâ€™s theory of anxiety and defense mechanisms. The main character in the story shows six types of defense mechanisms, such as; repression, denial, formation reaction, projection, regression, and rationalization. Keywords: anxiety, defense mechanisms, literary criticism, psychoanalysis